A modified metal organic framework material, a preparation method thereof and application of the modified metal organic framework material in adsorbing and detecting heavy metal Mn ions

CN116970185BActive Publication Date: 2026-10-27XI AN JIAOTONG UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310954782.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2026-10-27
Estimated Expiration
2043-07-31

AI Technical Summary

Technical Problem

[0005]为了克服上述现有技术的缺点,本发明的目的在于提供一种改性金属有机骨架材料及其制备方法和吸附检测重金属Mn离子的应用,以解决现有的金属有机骨架材料吸附容量小且无法实时监测吸附的技术问题

Benefits of technology

[0026]本发明公开的改性金属有机骨架材料的制备方法,同时选取2-氨基对苯二甲酸和乙二胺四乙酸作为改性修饰剂,取氯化锆(ZrCl4)和2-氨基对苯二甲酸(H2BDC-NH2)溶解于溶剂中,同时加入冰乙酸(CH3COOH),通过水热合成引入氨基(-NH2)得到具有荧光效应的NH2-UiO-66吸附材料,通过水热方式将NH2-UiO-66接枝EDTA制备NH2-UiO-66-EDTA,采用水热合成方法得到可同步检测并吸附处理重金属Mn离子的吸附剂NH2-UiO-66-EDTA,锰离子(Mn2+)对于荧光具有猝灭作用,高浓度Mn2+会使得荧光强度变弱,EDTA对Mn2+的强效螯合可提高材料对于重金属离子Mn2+的吸附容量,同步实现Mn2+的吸附检测一体化。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116970185B_ABST
    Figure CN116970185B_ABST
Patent Text Reader

Abstract

The application discloses a modified metal organic framework material and a preparation method and application of the modified metal organic framework material in adsorbing and detecting heavy metal Mn ions, and belongs to the field of heavy metal ion treatment of wastewater. 2-amino terephthalic acid and ethylenediaminetetraacetic acid are simultaneously selected as modified modifiers, and an adsorbent NH2-UiO-66-EDTA capable of synchronously detecting and adsorbing and treating heavy metal Mn ions is obtained by using a hydrothermal synthesis method. The modification of amino (-NH2) in the adsorbent makes the adsorbent have fluorescence detection performance, and the modification of EDTA improves the adsorption capacity of the adsorbent to heavy metal manganese ions. The adsorbent has high adsorption capacity and excellent fluorescence detection performance, and has a good application scene in the adsorption and detection of heavy metal manganese ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of adsorption material synthesis technology, specifically relating to a modified metal-organic framework material, its preparation method, and its application in adsorbing and detecting heavy metal Mn ions. Background Technology

[0002] Heavy metal Mn in industrial wastewater 2+ Although present in trace amounts, it is highly toxic and can severely pollute the environment and endanger human health. For example, excessive amounts of Mn... 2+ The presence of Mn in water can lead to neurological deficits and lung diseases, and hinder intellectual development and normal growth in infants. Therefore, it is essential to detect Mn in water promptly and accurately. 2+ Ion concentration ensures health and safety.

[0003] Currently, effective methods for removing heavy metal ions from industrial wastewater include flocculation, chemical precipitation, membrane filtration, ion exchange, and adsorption. Among these, adsorption is considered the most economical and effective method for removing heavy metals from water. Based on the characteristics of adsorption, constructing ideal adsorption materials with a large specific surface area and selective interaction with heavy metal ions is key to the adsorption and removal of heavy metal ions from water.

[0004] Compared to traditional adsorbent materials, metal-organic frameworks (MOFs) possess larger specific surface areas and are easier to modify by grafting functional groups, significantly improving selective adsorption and removal efficiency, and have attracted much attention in the field of heavy metal ion adsorption. Patent CN111346609A discloses an adsorbent material with a removal rate of over 90% for heavy metal ions in industrial wastewater containing dyes and heavy metal ions, but it cannot provide real-time data on heavy metal ion concentration changes. Patent CN113234235A discloses an MOF material for lead detection, but its adsorption and removal effects are not significant. Clearly, materials that can simultaneously detect and possess both adsorption and removal properties are more suitable for practical needs. Summary of the Invention

[0005] In order to overcome the shortcomings of the prior art, the present invention aims to provide a modified metal-organic framework material, its preparation method and its application in adsorption and detection of heavy metal Mn ions, so as to solve the technical problems of small adsorption capacity and inability to monitor adsorption in real time of existing metal-organic framework materials.

[0006] To achieve the above objectives, the present invention employs the following technical solution:

[0007] This invention discloses a method for preparing a modified metal-organic framework material, comprising the following steps:

[0008] 1) Dissolve disodium ethylenediaminetetraacetate in water and mix thoroughly to obtain a mixed solution. Disperse NH2-UiO-66 in the mixed solution by ultrasonication. Then carry out a hydrothermal reaction at 60°C. After the hydrothermal reaction is complete, cool to room temperature to obtain the product mother liquor.

[0009] 2) The mother liquor of the product is centrifuged and the solid-liquid separation is performed to obtain a solid crude product, which is then washed and dried to obtain the modified metal-organic framework material, namely NH2-UiO-66-EDTA.

[0010] Preferably, in step 1), the molar ratio of disodium ethylenediaminetetraacetate to water is 1:(300-400).

[0011] More preferably, the molar ratio of disodium ethylenediaminetetraacetate to water is 1:359.

[0012] Preferably, in step 1), the mass ratio of disodium ethylenediaminetetraacetate to NH2-UiO-66 is (1-20):1.

[0013] More preferably, the mass ratio of disodium ethylenediaminetetraacetate to NH2-UiO-66 is 13.7:1.

[0014] Preferably, in step 1), the hydrothermal reaction time is 24 hours; in step 2), the drying is carried out under vacuum at a temperature of 60–100°C for 12 hours.

[0015] Preferably, the NH2-UiO-66 is prepared by the following method:

[0016] Step 1: Dissolve zirconium chloride and 2-aminoterephthalic acid completely in a solvent to obtain mixture A. Add glacial acetic acid to mixture A and mix well to obtain mixture B.

[0017] Step 2: Mixture B is subjected to hydrothermal reaction at 130-180℃, cooled to room temperature to obtain product mother liquor C, centrifuged and separated into solid and liquid to obtain crude solid product, washed and treated with methanol to remove solvent, centrifuged to recover solid sample C, and dried to obtain NH2-UiO-66.

[0018] More preferably, in step 1, the solvent is N,N-dimethylformamide, and the molar ratio of zirconium chloride, 2-aminoterephthalic acid and N,N-dimethylformamide is 1:1:(10-25).

[0019] More preferably, the molar ratio of zirconium chloride, 2-aminoterephthalic acid and N,N-dimethylformamide is 1:1:18.2.

[0020] More preferably, in step 1, the volume ratio of glacial acetic acid to N,N-dimethylformamide is 1:(10-30).

[0021] More preferably, the volume ratio of glacial acetic acid to N,N-dimethylformamide is 1:24.3.

[0022] Preferably, in step 2, the hydrothermal reaction time is 24 hours; the solid crude product is washed with N,N-dimethylformamide, and then soaked in methanol for three days, with the methanol being replaced daily until N,N-dimethylformamide is completely removed; the drying is performed by vacuum drying at a temperature of 80-100°C for 12 hours.

[0023] The present invention also discloses a modified metal-organic framework material prepared by the above-described preparation method.

[0024] This invention also discloses the application of the above-mentioned modified metal-organic framework material for the adsorption and detection of heavy metal Mn ions, specifically for the adsorption and detection of Mn in solutions with a pH of 6–8. 2+

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] This invention discloses a method for preparing modified metal-organic framework materials. 2-Aminoterephthalic acid and ethylenediaminetetraacetic acid are selected as modifying agents. Zirconium chloride (ZrCl4) and 2-aminoterephthalic acid (H2BDC-NH2) are dissolved in a solvent, and glacial acetic acid (CH3COOH) is added. Amino groups (-NH2) are introduced via hydrothermal synthesis to obtain NH2-UiO-66 adsorbent material with fluorescence. NH2-UiO-66 is then grafted with EDTA via hydrothermal synthesis to prepare NH2-UiO-66-EDTA. The hydrothermal synthesis method yields NH2-UiO-66-EDTA, an adsorbent capable of simultaneously detecting and adsorbing heavy metal Mn ions. 2+ Mn has a quenching effect on fluorescence, and high concentrations of Mn 2+ It will weaken the fluorescence intensity; EDTA has a negative effect on Mn. 2+ The strong chelation effect can improve the material's ability to bind heavy metal ions Mn. 2+ The adsorption capacity of Mn was simultaneously achieved. 2+ The adsorption detection is integrated.

[0027] The modified metal-organic framework material NH2-UiO-66-EDTA prepared by the above method of the present invention was used for the heavy metal ion Mn 2+ Adsorption detection of Mn 2+ The metal-organic framework material NH2-UiO-66-EDTA was added to the solution for adsorption. As the reaction proceeded, Mn2+ As the concentration decreases, the fluorescence effect of the material gradually weakens, achieving the desired fluorescence for Mn. 2+ Real-time adsorption detection of solution, this invention for Mn 2+ It exhibits high adsorption capacity, and the extent of the reaction can be determined by a simple fluorescence effect. Attached Figure Description

[0028] Figure 1 This is the XRD pattern of the modified metal-organic framework material NH2-UiO-66-EDTA involved in this invention;

[0029] Figure 2 This is an N2 adsorption-desorption curve of the modified metal-organic framework material NH2-UiO-66-EDTA involved in this invention; wherein, (a) is UiO-66; (b) is NH2-UiO-66-EDTA;

[0030] Figure 3 The present invention relates to the modified metal-organic framework material NH2-UiO-66-EDTA, used at a dosage of 0.5 g / L and pH = 6, for different concentrations of Mn. 2+ Adsorption isotherms of the solution;

[0031] Figure 4 The modified metal-organic framework material NH2-UiO-66-EDTA involved in this invention adsorbs different concentrations of Mn under the conditions of 0.5 g / L and pH = 6. 2+ Fluorescence effect after solution treatment. Detailed Implementation

[0032] To enable those skilled in the art to better understand the present invention, the technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of the present invention.

[0033] It should be noted that the terms "first," "second," etc., in the specification, claims, and accompanying drawings of this invention are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such data can be interchanged where appropriate so that the embodiments of the invention described herein can be implemented in orders other than those illustrated or described herein. Furthermore, the terms "comprising" and "having," and any variations thereof, are intended to cover a non-exclusive inclusion; for example, a process, method, system, product, or apparatus that comprises a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to such processes, methods, products, or apparatus.

[0034] The present invention will now be described in further detail with reference to the accompanying drawings:

[0035] This invention discloses a modified metal-organic framework material and its preparation method, comprising the following steps:

[0036] 1) Dissolve a certain mass of zirconium chloride (ZrCl4) and 2-aminoterephthalic acid (H2BDC-NH2) in N,N-dimethylformamide (DMF) and stir until homogeneous to obtain mixture A; rapidly add glacial acetic acid (CH3COOH) dropwise into mixture A and mix until homogeneous to obtain mixture B;

[0037] 2) Transfer the mixture B to a polytetrafluoroethylene hydrothermal reactor and react for a certain period of time. After the reaction is complete, allow the hydrothermal reactor to cool naturally to room temperature to obtain the product mother liquor C. Pour the product mother liquor C into a centrifuge tube and centrifuge to separate the solid and liquid to obtain the solid crude product C. Then wash the crude product C with DMF to remove unreacted reactants. Soak the crude product C in the solvent methanol (MeOH) for three days, changing the MeOH daily to remove DMF. After centrifugation, obtain the solid sample C. Vacuum dry the solid sample C to obtain product C, which is NH2-UiO-66.

[0038] 3) Dissolve a certain mass of disodium ethylenediaminetetraacetate (EDTA-2Na) in deionized water (H2O), stir until homogeneous, and obtain mixture D; take a certain mass of product C and ultrasonically disperse it in mixture D to obtain mixture E;

[0039] 4) Transfer the mixture E to a polytetrafluoroethylene hydrothermal reactor for a certain reaction time; after the reaction is complete, allow the hydrothermal reactor to cool naturally to room temperature to obtain the product mother liquor F. Pour the product mother liquor F into a centrifuge tube and centrifuge to separate the solid and liquid to obtain the solid crude product F; wash the crude product F with deionized water and centrifuge to recover the solid sample F; vacuum dry the solid sample F to obtain product F, which is NH2-UiO-66-EDTA.

[0040] Preferably, in step 1), the molar ratio of ZrCl4:H2BDC-NH2:DMF is 1:1:18.2.

[0041] Preferably, in step 1), the volume ratio of CH3COOH:DMF is 1:24.3.

[0042] Preferably, in step 2), the hydrothermal temperature is 130–180°C and the hydrothermal time is 24 hours.

[0043] Preferably, in step 2), the vacuum drying temperature is 80-100℃ and the drying time is 12h.

[0044] Preferably, in step 3), the molar ratio of EDTA-2Na:H2O is 1:359.

[0045] Preferably, in step 3), the mass ratio of EDTA-2Na:NH2-UiO-66 is 13.7:1.

[0046] Preferably, in step 4), the hydrothermal temperature is 60°C and the hydrothermal time is 24 hours.

[0047] Preferably, in step 4), the vacuum drying temperature is 60–100°C and the drying time is 12 hours.

[0048] The modified metal-organic framework material (NH2-UiO-66-EDTA) prepared in this invention is used for the adsorption and detection of heavy metal ions. Under certain conditions, the NH2-UiO-66-EDTA is used to adsorb different concentrations of Mn. 2+ The solution was then subjected to fluorescence detection, specifically:

[0049] Take different concentrations of Mn 2+ The solution was prepared, pH adjusted, and then 0.5 g / L of adsorbent was added. The mixture was magnetically stirred for 24 hours to reach adsorption equilibrium. After the reaction was complete, the supernatant was collected using a syringe and a 0.45 μm filter. The solution was diluted 100 times, and the ion concentrations before and after adsorption were measured using an atomic absorption spectrophotometer to calculate the adsorption capacity of the material for metal ions. The adsorbed material was centrifuged and dried, and its fluorescence intensity was measured using a fluorescence spectrometer.

[0050] Example 1

[0051] 1) Dissolve 1.49 g of zirconium chloride (ZrCl4) and 1.16 g of 2-aminoterephthalic acid (H2BDC-NH2) in 90 mL of N,N-dimethylformamide (DMF) and stir for 2 h until homogeneous to obtain mixture A; rapidly add 3.7 mL of glacial acetic acid (CH3COOH) dropwise to mixture A and mix thoroughly to obtain mixture B;

[0052] 2) Transfer the mixture B to a 100 mL polytetrafluoroethylene hydrothermal reactor and place it in an electrically heated oven at 150 °C for 24 h. After the reaction is complete, allow the hydrothermal reactor to cool naturally to room temperature to obtain the mother liquor C. Pour the mother liquor C into a centrifuge tube and centrifuge to separate the solid and liquid to obtain the crude solid product C. Then wash the crude product C with DMF to remove unreacted reactants. Soak the crude product C in methanol (MeOH) for three days, changing the MeOH three times a day to remove DMF. Centrifuge to recover the solid sample C. Dry the solid sample C under vacuum at 100 °C for 12 h to obtain product C, which is NH2-UiO-66.

[0053] 3) Dissolve 5.2g of disodium ethylenediaminetetraacetate (EDTA-2Na) in 100mL of deionized water (H2O) and stir for 1h until homogeneous to obtain mixture D; take 0.38g of product C and sonicate for 10min to disperse it in mixture D to obtain mixture E;

[0054] 4) Transfer the mixture E to a polytetrafluoroethylene hydrothermal reactor and place it in an electrically heated oven at 60°C for 24 hours. After the reaction is complete, allow the hydrothermal reactor to cool naturally to room temperature to obtain the mother liquor F. Pour the mother liquor F into a centrifuge tube and centrifuge to separate the solid and liquid to obtain the crude solid product F. Wash the crude product F with deionized water and centrifuge to recover the solid sample F. Dry the solid sample F under vacuum at 60°C for 12 hours to obtain product F, which is NH2-UiO-66-EDTA.

[0055] XRD analysis was performed on NH2-UiO-66 and NH2-UiO-66-EDTA prepared in this embodiment, as follows: Figure 1 As shown, the diffraction peaks of the prepared material are consistent with those of Uio-66, indicating that the modified material did not change the crystal form and structural stability of the original framework.

[0056] The modified metal-organic framework material NH2-UiO-66-EDTA prepared in this embodiment is used for the adsorption and detection of heavy metal ions.

[0057] Take 25 mL of Mn with a concentration of 50–350 mg / L 2+ The solution was adjusted to pH 6, and then 0.5 g / L of the adsorbent NH₂-UiO-66-EDTA was added. The mixture was magnetically stirred for 24 hours to reach adsorption equilibrium. After the reaction was complete, the supernatant was collected using a syringe and a 0.45 μm filter. The solution was diluted 100 times, and the ion concentrations before and after adsorption were measured using an atomic absorption spectrophotometer to calculate the adsorption capacity of the material for metal ions. Detailed results are as follows... Figure 3As shown, the adsorption capacity of the modified material increases with increasing solution concentration. This is because, with increasing solution concentration, heavy metal ions readily diffuse onto the surface of the adsorbent and further bind to the surface active sites. As the solution concentration increases, the active sites gradually approach saturation, thus the adsorption isotherm gradually flattens. Fitting the adsorption curve using the Langmuir model yields the adsorption capacity of NH2-UiO-66-EDTA on Mn. 2+ The maximum adsorption capacity can reach 105.6 mg / g.

[0058] Example 2

[0059] 1) Dissolve 1.49 g of zirconium chloride (ZrCl4) and 1.66 g of 2-aminoterephthalic acid (H2BDC-NH2) in 90 mL of N,N-dimethylformamide (DMF) and stir until homogeneous to obtain mixture A; then rapidly add 3.7 mL of glacial acetic acid (CH3COOH) dropwise to mixture A and mix thoroughly to obtain mixture B;

[0060] 2) Transfer the mixture B to a 100 mL polytetrafluoroethylene hydrothermal reactor and place it in an electrically heated oven at 150 °C for 24 h. After the reaction is complete, allow the hydrothermal reactor to cool naturally to room temperature to obtain the mother liquor C. Pour the mother liquor C into a centrifuge tube and centrifuge to separate the solid and liquid to obtain the crude solid product C. Then wash the crude product C with DMF to remove unreacted reactants. Soak the crude product C in methanol (MeOH) for three days, changing the MeOH three times a day to remove DMF. Centrifuge to recover the solid sample C. Dry the solid sample C under vacuum at 100 °C for 12 h to obtain product C, which is NH2-UiO-66.

[0061] 3) Dissolve 5.2g of disodium ethylenediaminetetraacetate (EDTA-2Na) in 100mL of deionized water (H2O) and stir for 1h until homogeneous to obtain mixture D; take 0.38g of product C and ultrasonically disperse it in mixture D to obtain mixture E;

[0062] 4) Transfer the mixture E to a polytetrafluoroethylene hydrothermal reactor and place it in an electrically heated oven at 60°C for 24 hours. After the reaction is complete, allow the hydrothermal reactor to cool naturally to room temperature to obtain the mother liquor F. Pour the mother liquor F into a centrifuge tube and centrifuge to separate the solid and liquid to obtain the crude solid product F. Wash the crude product F with deionized water and centrifuge to recover the solid sample F. Dry the solid sample F under vacuum at 60°C for 12 hours to obtain product F, which is NH2-UiO-66-EDTA.

[0063] The modified metal-organic framework material (NH2-UiO-66-EDTA) prepared in this embodiment is used for the adsorption and detection of heavy metal ions:

[0064] Take 100 mL of Mn at concentrations of 50, 100, 200, and 300 mg / L respectively. 2+ The solution was adjusted to pH 6, and then 0.5 g / L of adsorbent was added. The mixture was magnetically stirred for 24 h to reach adsorption equilibrium. After the reaction was complete, the adsorbed material was centrifuged and dried, and the fluorescence intensity of the adsorbed material was detected using a fluorescence spectrometer. Detailed results are as follows: Figure 4 As shown, the NH2-UiO-66-EDTA material without adsorption exhibits strong fluorescence properties. After adsorbing manganese ions, its fluorescence properties weaken, and the higher the concentration of adsorbed manganese ions, the weaker the fluorescence intensity. Therefore, during the adsorption process, the intensity of fluorescence can be used to determine whether an adsorption reaction has occurred, providing real-time feedback.

[0065] Comparative Example 1

[0066] 1) Dissolve 1.49 g of zirconium chloride (ZrCl4) and 1.06 g of terephthalic acid (H2BDC) in 90 mL of N,N-dimethylformamide (DMF) and stir for 2 h until homogeneous to obtain mixture A; rapidly add 3.7 mL of glacial acetic acid (CH3COOH) dropwise to mixture A and mix thoroughly to obtain mixture B;

[0067] 2) Transfer the mixture B to a 100 mL polytetrafluoroethylene hydrothermal reactor and place it in an electric heating oven at 150 °C for 24 h. After the reaction is complete, allow the hydrothermal reactor to cool naturally to room temperature to obtain the product mother liquor C. Pour the product mother liquor C into a centrifuge tube and centrifuge to separate the solid and liquid to obtain the crude solid product C. Then wash the crude product C with DMF to remove unreacted reactants. Soak the crude product C in methanol (MeOH) for three days, changing the MeOH three times a day to remove DMF. Centrifuge to recover the solid sample C. Dry the solid sample C under vacuum at 100 °C for 12 h to obtain product C, which is UiO-66.

[0068] Nitrogen adsorption-desorption analysis was performed on UiO-66 and NH2-UiO-66-EDTA prepared in Example 1, as follows: Figure 2 As shown, (a) represents UiO-66; (b) represents NH2-UiO-66-EDTA. The curves exhibit a typical Type I structure, indicating that the material possesses a microporous structure, and the introduction of EDTA and -NH2 did not alter the pore structure. Calculations based on the characterization results show that the specific surface area of ​​UiO-66 is as high as 1236.6 m². 2 / g, the specific surface area of ​​NH2-UiO-66-EDTA can reach 378.7m². 2 / g, the specific surface area of ​​the NH2-UiO-66-EDTA modified material is smaller than that of UiO-66 because the introduction of -EDTA blocks the pores. At the same time, -NH2 can form intramolecular and intermolecular hydrogen bonds with the abundant -COOH functional groups in the material, resulting in a certain degree of aggregation. However, -EDTA and -NH2 bring more functional groups, which can provide more adsorption sites, thus still having good adsorption characteristics.

[0069] In summary, this invention simultaneously selects 2-aminoterephthalic acid and ethylenediaminetetraacetic acid as modifying agents, and uses a hydrothermal synthesis method to obtain an adsorbent NH2-UiO-66-EDTA that can simultaneously detect and adsorb heavy metal Mn ions. The modification of the amino group (-NH2) in this adsorbent endows it with fluorescent detection properties, while the EDTA modification enhances its adsorption capacity for heavy metal manganese ions. The adsorbent of this invention exhibits high adsorption capacity and excellent fluorescent detection performance, making it suitable for applications in the adsorption and detection of heavy metal manganese ions.

[0070] The above content is only for illustrating the technical concept of the present invention and should not be construed as limiting the scope of protection of the present invention. Any modifications made to the technical solution based on the technical concept proposed in this invention shall fall within the scope of protection of the claims of this invention.

Claims

1. A method for preparing a modified metal-organic framework material, characterized in that, Includes the following steps: 1) Dissolve disodium ethylenediaminetetraacetate in water and mix thoroughly to obtain a mixed solution. Disperse NH2-UiO-66 in the mixed solution by ultrasonication. Then carry out a hydrothermal reaction at 60°C. After the hydrothermal reaction is complete, cool to room temperature to obtain the product mother liquor. 2) The mother liquor of the product is centrifuged and the solid-liquid separation is performed to obtain a solid crude product, which is then washed and dried to obtain the modified metal-organic framework material, namely NH2-UiO-66-EDTA; In step 1), the mass ratio of disodium ethylenediaminetetraacetate to NH2-UiO-66 is (1~20):1, and the molar ratio of disodium ethylenediaminetetraacetate to water is 1:(300~400).

2. The method for preparing the modified metal-organic framework material according to claim 1, characterized in that, In step 1), the hydrothermal reaction time is 24 h; in step 2), the drying is carried out under vacuum at a temperature of 60~100℃ for 12 h.

3. The method for preparing the modified metal-organic framework material according to claim 1, characterized in that, The NH2-UiO-66 is prepared by the following method: Step 1: Dissolve zirconium chloride and 2-aminoterephthalic acid completely in a solvent to obtain mixture A. Add glacial acetic acid to mixture A and mix well to obtain mixture B. Step 2: The mixture B is subjected to hydrothermal reaction at 130~180℃ and cooled to room temperature to obtain the product mother liquor C. The solid crude product is obtained by centrifugation and solid-liquid separation. The solid crude product is washed and treated with methanol to remove the solvent. The solid sample C is recovered by centrifugation and dried to obtain NH2-UiO-66.

4. The method for preparing the modified metal-organic framework material according to claim 3, characterized in that, In step 1, the solvent used is N,N-dimethylformamide, and the molar ratio of zirconium chloride, 2-aminoterephthalic acid and N,N-dimethylformamide is 1:1:(10~25).

5. The method for preparing the modified metal-organic framework material according to claim 4, characterized in that, In step 1, the volume ratio of glacial acetic acid to N,N-dimethylformamide is 1:(10~30).

6. The method for preparing the modified metal-organic framework material according to claim 3, characterized in that, In step 2, the hydrothermal reaction time is 24 h; the solid crude product is washed with N,N-dimethylformamide, and then soaked in methanol for three days, with the methanol being replaced daily until N,N-dimethylformamide is completely removed; the drying is carried out under vacuum at a temperature of 80~100℃ for 12 h.

7. A modified metal-organic framework material prepared by any one of claims 1 to 6.

8. The application of the modified metal-organic framework material according to claim 7 for the adsorption and detection of heavy metal Mn ions, characterized in that, Mn adsorption detection in solutions with pH values ​​of 6–8 2+ The modified metal-organic framework material for Mn 2+ The maximum adsorption capacity reaches 105.6 mg / g.

Citation Information

Patent Citations

  • Adsorbing material for heavy metal-containing dye wastewater and preparation method thereof

    CN111346609A

  • Preparation method of medium-tetra (4-carboxy phenyl) zinc porphyrin-MOF material for detecting lead

    CN113234235A

  • Novel metal-organic framework material and preparing method and usage thereof

    CN107159128A

  • Preparation method of UIO-66-NH2 for detecting iron ions by fluorescence

    CN108593616A

  • Amino-functionalized luminescent metal organic framework as well as preparation method and application thereof

    CN115505131A